Gamification into the design of the e-3D online course - dos Reis, Susana Cristina; Linck, Anderson José Machado; Figueiredo, Max Flores; Pfeifer, Diéssica Lopes (Frontiers in Education, 2023)
Research in the fields of Education and Applied Linguistics points to the growth of studies on digital games and gamification in Brazil. On the other hand, studies that discuss digital teaching material do not provide guidelines on how to implement gamification into the design of digital teaching materials, mainly in language studies. Thus, this work presents practical guidelines for how to explore gamification in the design of language teaching materials based on the experience developed in the outreach project laboratory of online language teaching and learning at the Federal University of Santa Maria. This research reports a case study carried out in the English online 3D course offered in the modality of distance education. To exemplify how the gamification strategies have been implemented, we provide examples from the course’s material as well as bring the user’s evaluation about participating in a gamified online course. Results indicate that gamification strategies were underpinned by exploring mainly intrinsic and extrinsic gamification strategies included in the digital material design, as well as by tools used on Moodle Platform to get the students engaged in the language learning process. On the other hand, this empirical study has shown the necessity of including more narrative strategies into the content proposed in the online course as an alternative to getting the students to explore meaningful learning by problem-solving in branching scenarios proposed inside the Moodle platform.